Refractory Celiac Disease Type II: A Case Report and Literature Review - Chibbar, Richa; Nostedt, Jordan; Mihalicz, Dana; Deschenes, Jean; McLean, Ross; Dieleman, Levinus A. (Frontiers in Medicine, 2020)
We present an unusual case of 68-year-old male, who presented with acute abdomen, ulcerative jejunitis with perforation, and two months later with perforation of the sigmoid colon. We will also discuss difficulties in the delay in diagnosis of refractory celiac disease (RCD), specifically the atypical presentation, multiple surgeries, the consecutive failure of distinct therapeutic options, and multiple complications that occurred within the three months since first presentation.